Attenuation of ER stress prevents post-infarction-induced cardiac rupture and remodeling by modulating both cardiac apoptosis and fibrosis. (5th January 2015) - Luo, Tao; Kim, Jin Kyung; Chen, Baihe; Abdel-Latif, Ahmed; Kitakaze, Masafumi; Yan, Liang
Highlights: Endoplasmic reticulum (ER) stress is implicated in the pathophysiology of myocardial infarction (MI). ER stress induced by MI results in cardiac apoptosis and fibrosis. 4-PBA protects the heart from post-infarction-induced cardiac rupture and remodeling. Abstract: Endoplasmic reticulum (ER) stress is implicated in the pathophysiology of various cardiovascular diseases, but the role of ER stress in cardiac rupture and/or remodeling after myocardial infarction (MI) is still unclear. Here we investigated whether ER stress plays a major role for these processes in mice. We ligated the left coronary artery (LCA) without reperfusion in mice and administered either NaCl or 4-phenylbutyric acid (4-PBA, 20 mg/kg/d) intraperitoneally for 4 weeks. Cardiac rupture rates during the first week of MI were 37.5% and 18.2% in the control and 4-PBA groups, respectively. The extent of ventricular aneurysm and fibrosis was less, and the cardiac function better, in the 4-PBA group compared with the control group. The protein levels of ER stress markers in the heart tissues of the control group remained elevated during the entire 4-week period after MI, while pro-apoptotic proteins mainly increased in the early phase, and the pro-fibrotic proteins markedly increased in the late phase post MI; 4-PBA decreased all of these protein levels. In the primary cultured neonatal rat cardiomyocytes or fibroblasts, hypoxia (3% O2 ) increased the number of apoptotic cardiomyocytes and promoted the proliferation and migration of fibroblasts, all of which were attenuated by 4-PBA (0.5 mM). These findings indicate that MI induces ER stress and provokes cardiac apoptosis and fibrosis, culminating in cardiac rupture and remodeling, and that the attenuation of ER stress could be an effective therapeutic target to prevent post-MI complications.